HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN BEROBAT RUTIN PADA PASIEN TUBERCULOSIS PARU DI RUANG POLIKLINIK RUMAH SAKIT AMINAH KOTA TANGERANG - Komariah, Siti; Simanullang, Rostime Hermayerni (Indonesian Trust Health Journal, 2021)
Tuberculosis is a direct infectious disease caused by TB bacteria, namely Mycobacterium tuberculosis which generally attacks lung tissue, but can also attack other organs. Pulmonary TB can affect anyone, especially those of productive age or still actively working (15-50 years) and children. This study aims to identify the relationship between family support and adherence to routine medication in pulmonary TB patients. The population of this study were all pulmonary TB patients in the Polyclinic of Aminah Hospital, Tangerang City with a total sample of 54 people who were taken using random sampling technique. The research method used is quantitative research using a correlation design to determine the correlation between variables and data analysis is carried out using the Spearman correlation test. From the results of the statistical analysis of the Spearman Rank test, the p value = 0.000 was obtained. or p value < 0.05. From the results of the study, it can be concluded that there is a relationship between family support and adherence to routine treatment in pulmonary TB patients in the Polyclinic Room of Aminah Hospital, Tangerang City in 2021, the value of r = 0.873 which means that there is a significant or very strong relationship between family support for the treatment of pulmonary TB patients. on Compliance with Routine Medication in the Polyclinic Room of Aminah Hospital, Tangerang City in 2021. Abstrak Tuberkulosis adalah penyakit menular langsung yang disebabkan oleh kuman TB yaitu Mycobacterium Tuberculosis yang pada umumnya menyerang jaringan paru, tetapi dapat juga menyerang organ lainya. TB paru dapat menyerang siapa saja, terutama usia produktif atau masih aktif bekerja (15-50 tahun) dan anak-anak. Penelitian ini bertujuan untuk mengidentifikasi hubungan dukungan keluarga tehadap kepatuhan berobat rutin pada pasien TB paru. Populasi penelitian ini adalah semua pasien TB paru di ruang poliklinik Rumah Sakit Aminah Kota Tangerang dengan jumlah sampel sebanyak 54 orang yang diambil dengan menggunakan teknik random sampling. Metode penelitian yang digunakan yaitu penelitian kuantitatif dengan menggunakan desain korelasi untuk mengetahui korelasi antara variabel dan analisis data di lakukan menggunakan uji korelasi spearman. Dari hasil analisa uji statistik Spearman Rank test maka di dapat nilai p = 0,000. atau nila p value < 0,05. Dari hasil penelitian dapat disimpulkan bahwa ada hubungan dukungan keluarga dengan kepatuhan berobat rutin pada pasien TB paru di ruang poliklinik Rumah Sakit Aminah Kota Tangerang Tahun 2021, nilai r = 0,873 yang berarti terdapat hubungan yang signifikan atau sangat kuat antara dukungan keluarga terhadap pengobatan pasien TB paru terhadap kepatuhan berobat rutin di ruang poliklinik Rumah Sakit Aminah Kota Tangerang Tahun 2021.